Interactive Games and Plays in Teaching Physics and Astronomy - Zhuldyzay Akimkhanova; Kunduz Turekhanova; Grzegorz P. Karwasz (MDPI AG, 2023)
Physics is a difficult subject in which to trigger interest in pupils, particularly in junior high school classes: this reflects in the results of maturity exams. Therefore, teachers, educators (and authorities deciding on CV contents) should search for new efficient methods, techniques, and contents corresponding to particular topics in physics. What can be done at the level of a single university (even if big) or school is to enrich standard lessons with new elements and observe how the responses of pupils change. In this article, the results of an implementation of interactive plays and games are presented for enhancing pupils' interest and rate of understanding in physics, astronomy, and engineering. The games were designed by authors and the contents were developed jointly at Nicolaus Copernicus University, Poland and al-Farabi Kazakh National University, Kazakhstan. Implementation was carried out both in schools (a secondary school in Almaty and one primary school in Torun) and in extra-school (secondary school students in Almaty, elementary and secondary school students in Torun, during university-based activities) environments. A preliminary analysis of the didactical efficiency is given. We observed a positive reception of the majority of the didactical means that we proposed. These observations will serve us for further (and possibly permanent) enrichment of forms and contents of teaching physics and astronomy.